Evasion of Intracellular DNA Sensing by Human Herpesviruses - Bhowmik, Debipreeta; Zhu, Fanxiu (Frontiers in Cellular and Infection Microbiology, 2021)
Sensing of viral constituents is the first and critical step in the host innate immune defense against viruses. In mammalian cells, there are a variety of pathogen recognition receptors (PRRs) that detect diverse pathogen-associated molecular patterns (PAMPs) including viral RNA and DNA. In the past decade, a number of host DNA sensors have been discovered and the underlying sensing mechanisms have been elucidated. Herpesviruses belong to a large family of enveloped DNA viruses. They are successful pathogens whose elaborate immune evasion mechanisms contribute to high prevalence of infection among their hosts. The three subfamilies of herpesviruses have all been found to employ diverse and overlapping strategies to interfere with host DNA sensing. These strategies include masking viral DNA or the DNA sensor, degradation of the DNA sensor, and post-transcriptional modification of the DNA sensor or its adaptor protein. In this review, we will discuss the current state of our knowledge on how human herpesviruses use these strategies to evade DNA-induced immune responses. Comprehensive understanding of herpesvirus immune-evasion mechanisms will aid in the development of vaccines and antivirals for herpesvirus-associated diseases.